Genetic analyses for the restoration of the Beluga sturgeon (Huso huso) in the Po river basin - Caruso, Chiara (Università degli studi di Padova, 2017)
The Beluga sturgeon (Huso huso) is a locally-extinct species in the Adriatic region, mainly due to anthropic factors. In order to successfully re-introduce this species, strong genetic bases are needed to set up a proper reintroduction plan that will lead to achieve a self-sustaining population as genetically similar as possible to those previously living in the Adriatic basin. On this basis, a phylogeographic investigation was performed at a mitochondrial level (for subsequent comparison with museum samples of the Adriatic population) in 119 Beluga specimens from 5 non-extinct populations from Black Sea and Caspian Sea basins. At a nuclear level, 110 specimens were analyzed at microsatellite markers and 54 at SNP loci through genome wide 2b-RAD approach. Based on genetic analyses of a 367 bp region of the mitochondrial D-loop, of 16 microsatellite loci and of 4736 polymorphic loci from RAD-seq, a significant geographically-related structure between Black Sea and Caspian Sea was observed. These analyses have shown the lack of a clear-cut differentiation of the population from the Sea of Azov from all the other populations, probably as result of the combined effect of the connection with the Black Sea and of the intensive release of individuals originating from the Caspian Sea basin. In this study, two distinct haplotypes of Adriatic Beluga have been identified from two museum specimens of H. huso. These haplotypes differed from all the 39 haplotypes identified in contemporary populations. Although the lack of shared haplotypes is not sufficient to demonstrate the existence of a former genetically distinct population in the Adriatic basin, this hypothesis is supported by the fact that the two museum haplotypes observed in three individuals were observed only in the Adriatic and were very similar one to each other. Two molecular tools have been developed for both the conservation and management of aquaculture stocks: 1) a species-specific nuclear tool for the identification of the Beluga based on a diagnostic SNP ...